Hung up on Judas: A Case Study on the Pragmatic Usage of Religious Iconography in Legal Manuscripts of the Institutiones - Lagreou, Helena (Eikón / Imago, 2023)
This article serves both as survey of illuminated manuscripts of the Institutiones and an analysis of the links between the iconography of criminal law and the model of Judas hanged. This investigation is based on the study of all digitalised manuscripts of the Institutiones. The corpus is composed of manuscripts ranging from the fifth to fifteenth century, produced all over Europe. The study elucidates how illuminated manuscript boomed during the thirteenth century, with Bologna at its heart. The production continued growing until the fourteenth century, to eventually die down during the fifteenth century. The world of legal manuscript’s illumination was Bologna-centric, however, some competitors, namely France and Germany, offered a visual counterpoint to understand this great iconography. When developing iconographic cycles around criminal law, two approaches existed. The approach developed in Northern Italy incorporated the representation of either a decapitation or a presentation of a prisoner. These illuminators created a specific iconography to further a distinctive visual identity within the field of legal manuscripts, whereas the rest of Europe adopted uniformly the image of a hanged man. This form of depiction takes for its model the motif of Judas hanged, heavily linking criminality to religion.